Kinematics and aerodynamics of in-flight drinking in bats - Maitra, Abhradeep; Kim, Seong Jin; Sayani, Naila; Hooshanginejad, Alireza; Mueller, Rolf; Wang, Z. Jane; Jung, Sunghwan (The Royal Society, 2025)
Bats, the only mammals with powered flight, provide inspiration to engineer highly manoeuvrable flapping wing aerial vehicles due to their ability in performing several complex manoeuvres. While straight flight manoeuvres have been extensively studied, drinking flight manoeuvres have not. We have studied two insectivorous bat species in terms of wing kinematics and aerodynamics during drinking flight: Hipposideros pratti and Rhinolophus ferrumequinum. During drinking, both bat species decrease their flapping amplitude and simultaneously increase their flapping frequency. The flapping angle during drinking flight manoeuvre is higher throughout the wingbeat compared with straight flight manoeuvre, while the sweep angle variation is reduced. Furthermore, the wing attains the most folded state earlier in the wingbeat during in-flight drinking. In addition, the angle of attack on the handwing at the end of downstroke is higher by almost 30 degrees-40 degrees in drinking flight indicating an active control to manipulate the aerodynamic forces as per the requirements of the manoeuvre. Finally, our force analysis reveals that the lift coefficient for drinking flight is more than twice that for straight flight. We discuss the potential role of ground effect in this lift enhancement.